Traditional Based Education Basandi Syarak Syarak Basandi Kitabullah Facing the Era of Smart Society 5.0 - Siska Tresia Oktari; Darmansyah (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Education is a conscious effort that assists humans in increasing their intellectual and mental abilities in increasing creativity as individuals and social beings in facing and adapting to changes and developments of the times. Until now, humans have arrived at the era of smart society 5.0 which is marked by the increasingly centralized role of technology in human life. The concept of smart society 5.0 allows humans to live side by side with technology in order to improve the quality of life in a sustainable manner. The religion of Islam has never prevented its followers from following the progress and developments of the times, including advances in communication technology. Many Minangkabau people embrace Islam. Basandi Syarak Syarak Basandi Kitabullah adat is a guideline for the Minangkabau tribe in carrying out their daily lives. Basandi Syarak Syarak Basandi Kitabullah adat is a hereditary culture that is firmly held by the Minangkabau people.